The Role of Recombinant DNA Technology in the Production of Insulin and Other Biopharmaceuticals - Hussein, Yousif Karim; Al-Asady, Suaad Mudhaher Habeeb Hassan; Abed, Fatima Zuhair Hamzah; Ati, Afaf Raad (American Journal of Botany and Bioengineering, 2025)
The invention of recombinant DNA technology provides a versatile way for generating proteins from cloned genes. Insulin was the first recombinant therapeutic protein widely used by millions of diabetes patients worldwide. Today, recombinant protein production continues to play a vital role in biopharmaceutical manufacture, providing at least 30% of the pharmaceuticals in the pipeline. It underpins the production of a large number of these drugs that have received regulatory approval and have become available worldwide for the treatment of a range of diseases. At the beginning of the DNA era in the 1970s, scientists started to study the biology of DNA molecules in nature and also began to appreciate the tremendous additional utility of these molecules as vectors for assembling and transferring genetic information. In the 1970s, the main focus of biochemistry and molecular biology shifted from the study of single molecules into the construction of molecules from parts, reflecting a belief in the understanding of life at a molecular level through the synthesis and analysis of biological components. The era of recombinant DNA technology was based on harnessing of naturally occurring DNA in cells to create standardized plasmids that could be used to construct new genetic entities with defined properties. Changes to biological targets are carried out through decoupling of the process of assembly and analysis into separate events. Generating the fundamental recombinant DNA construct that can be used to produce the desired product at the industrial level requires considerable effort, and, normally, several iterations are necessary before the optimal clone is identified.